2013
DOI: 10.4161/cc.25622
|View full text |Cite
|
Sign up to set email alerts
|

The p27–Skp2 axis mediates glucocorticoid-induced cell cycle arrest in T-lymphoma cells

Abstract: Glucocorticoid therapy is an important treatment modality of hematological malignancies, especially T-cell acute lymphoblastic leukemia (T-ALL). Glucocorticoids are known to induce a cell cycle arrest and apoptosis in T-lymphoma cells. We could demonstrate that the cell cycle arrest induced by the synthetic glucocorticoid dexamethasone (Dex) clearly precedes apoptosis in human CEM T-ALL and murine S49.1 T-lymphoma cells. Cyclin D3 is strongly downregulated, whereas the CDK inhibitor p27Kip1 (p27) is strongly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…Consistently, upregulation of Skp2 in mice enhanced tumor growth in lymphoma (21), prostate cancer (19) and breast tumor (18). Importantly, high expression of Skp2 has been observed in a wider spectrum of cancers including lymphomas (22,23) (25)(26)(27)(28)(29), prostate (30,31) and gastric cancer (32), melanoma (33)(34)(35), hepatocarcinoma (36) and nasopharyngeal carcinoma (37,38). Skp2 was also highly expressed and was correlated with relapse, metastasis and survival in OS patients (39).…”
Section: Introductionmentioning
confidence: 73%
“…Consistently, upregulation of Skp2 in mice enhanced tumor growth in lymphoma (21), prostate cancer (19) and breast tumor (18). Importantly, high expression of Skp2 has been observed in a wider spectrum of cancers including lymphomas (22,23) (25)(26)(27)(28)(29), prostate (30,31) and gastric cancer (32), melanoma (33)(34)(35), hepatocarcinoma (36) and nasopharyngeal carcinoma (37,38). Skp2 was also highly expressed and was correlated with relapse, metastasis and survival in OS patients (39).…”
Section: Introductionmentioning
confidence: 73%
“…A recent publication demonstrated that Dex-induced cell cycle arrest was mediated by the p27-Skp2 axis in Dex-sensitive T-lymphoma cells. 38 Thus, further investigation is required to clarify the mechanism required to initiate Dex-induced cell cycle arrest in Dex-resistant lymphoid malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have revealed that the overexpression of Skp2 is associated with the progression of a variety of types of human cancer (22)(23)(24)(25). Functional deletion of Skp2 leads to stabilization of CDK inhibitors, which can subsequently induce cell-cycle delay or arrest (26,27 The aim of the study was to explore the role of Skp2 in colon carcinoma and to identify whether depletion of Skp2 by Skp2 RNA interference attenuates the proliferation and migration of colon carcinoma.…”
Section: Introductionmentioning
confidence: 99%